Prosecuting and Propagating Emotional Harm: The Criminalisation of HIV Nondisclosure in Canada - Katarina Bogosavljević; Jennifer M. Kilty (Canadian Journal of Law and Society)
This article explores emotional harm in the context of the criminalization of HIV nondisclosure in Canada. With the exception of Matthew Weait in the United Kingdom, few scholars have examined what harm means in cases of HIV nondisclosure. We conceptualize the harm that follows nondisclosure as an affective response to the “HIV positive Other” and argue that law creates a legal norm about what harm is and feels like in cases of HIV nondisclosure when there is no clear consensus about how harm should be defined. Mobilizing the sociology of emotions literature, we contend that criminalizing HIV nondisclosure engages affective, moral, and criminal censure to regulate the behaviours of people living with HIV/AIDS (PLWH), thus reproducing HIV stigma and propagating emotional harm for PLWH. Canada’s response to HIV nondisclosure should instead involve a transformative justice approach that avoids the harm of criminalization and imprisonment while recognizing the emotional harm experienced by complainants.